A construção do ator “Jesus Cristo” em cenas de o evangelho segundo Jesus Cristo, de José Saramago. Uma leitura semiótica - Saad, Tárcia Caires (2017)
This research aims to analyze the construction of the actor Jesus Cristo (Jesus Christ) in the novel O Evangelho segundo Jesus Cristo (The Gospel according to Jesus Christ), by José Saramago, using the theoretical framework of French Semiotics. Our study is justified by the fact that there are few researches in the Semiotic field on this author's work, which is greatly relevant in the literary scene worldwide. In the novel, we observed that the enunciator, through irony, deconstructs dogmas of the Christian-mythical discourse. The work reveals to us a new way of construction of Christ's subjectivity that is very polemic in contrast to his image created in the Christian Gospel. On that perspective, we analyze the way Jesus Cristo’s figure is constructed in two scenes of Saramago’s work, the lost sheep scene and the one of the boat. We observed especially its relationship with Deus (God) and Pastor - the latter is Diabo’s (Devil) anthroponym in the novel – focusing on the actancial, thematic and pathemic roles of the leading actor and the polemic-contractual relationships that are established with the other two actors.